Enhancement of Nutritional and Organoleptic Qualities in Biscuits through Substitution with Pumpkin Puree and Katuk Leaves - Barek, Theresia Dewi Kartini; Lestari, Retno Sri; Nadimin, Nadimin (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Biscuits, a popular snack, offer a platform for nutritional innovation by incorporating local food ingredients. This study explores the substitution of traditional ingredients with pumpkin puree and katuk leaves to develop enriched biscuits suitable for pregnant women and nursing mothers. Employing a Completely Randomized Design (CRD), the study varied the levels of pumpkin puree and katuk leaf substitutions across four formulations: F0 (0% pumpkin, 0% katuk leaves), F1 (40% pumpkin, 3% katuk leaves), F2 (45% pumpkin, 4% katuk leaves), and F3 (50% pumpkin, 5% katuk leaves). Conducted in Makassar City in 2023, the study utilized SPSS for data analysis. Results indicated that biscuits with pumpkin and katuk leaf substitutions showed enhanced antioxidant properties, evidenced by significant increases in phenolic compounds (p=0.003) and flavonoids (p<0.001). Additionally, these biscuits met the moisture and ash content standards set by SNI 2973:2011 and SNI 01-2973-1992, respectively. Organoleptically, the F1 biscuits were most preferred, scoring 783. In conclusion, substituting traditional biscuit ingredients with pumpkin puree and katuk leaves significantly improves the antioxidant activity, compliance with moisture and ash standards, and organoleptic quality of the biscuits.